2019
DOI: 10.1177/0300060519828522
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency catheter ablation for paroxysmal atrial fibrillation: outcomes during a 3-year follow-up period

Abstract: Objective This study was performed to observe the effect of radiofrequency catheter ablation (RFCA) in patients with paroxysmal atrial fibrillation (PAF) and to explore the risk factors for late recurrence of atrial fibrillation (LRAF) after a single RFCA session. Methods In this retrospective study, 243 patients with PAF underwent RFCA and were followed up regularly. Results At a median follow-up of 37 months after a single procedure, 60.5% of patients maintained sinus rhythm (SR), and at a median follow-up o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Although the operational risk of CA was reduced, the reduction in mortality and stroke was rarely reported. In addition, the adverse effects of ADT, such as thyroid dysfunction, caused 23% of patients to discontinue treatment, in addition to the accumulation of more serious side effects over the long term [ 12 , 17 , 20 , 21 ]. Although CA was superior to ADT in the first year, the long-term efficacy remains to be evaluated, which is key problem in all current RCT studies [ 2 , 8 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the operational risk of CA was reduced, the reduction in mortality and stroke was rarely reported. In addition, the adverse effects of ADT, such as thyroid dysfunction, caused 23% of patients to discontinue treatment, in addition to the accumulation of more serious side effects over the long term [ 12 , 17 , 20 , 21 ]. Although CA was superior to ADT in the first year, the long-term efficacy remains to be evaluated, which is key problem in all current RCT studies [ 2 , 8 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al (6) reported that more than two-thirds of AF recurrence were in the first year after single or multiple procedures. Other studies have also shown that the rate of early recurrence of AF (ERAF, defined as AF recurrence within a 3month blanking period) ranged from approximately 38.2-58.6% after a single ablation, and that ERAF significantly predicted late recurrence of AF (29)(30)(31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have confirmed the effectiveness and safety of catheter ablation in the treatment of paroxysmal atrial fibrillation (PAF) (4)(5)(6). Electrical isolation of the pulmonary vein (PV) is essential for catheter ablation of AF, which traditionally is achieved by radiofrequency catheter ablation (RCA) (7).…”
Section: Introductionmentioning
confidence: 99%
“…While catheter ablation reaches an almost 80% success rate at 12 months for paroxysmal AF patients in many recent trials, regardless of ablation strategy or ablation energy source, the long‐term success rates after ablation for persistent AF do not exceed 50%–55%. 6 , 7 , 8 , 9 , 10 , 11 , 12 This may be related to incomplete understanding of the underlying atrial substrate outside the pulmonary veins (PVs). Another possible explanation is that existing mapping technologies cannot reliably and accurately detect active versus passive and/or sources of significance in this patient population.…”
Section: Introductionmentioning
confidence: 99%
“…However, the treatment of persistent AF remains more challenging. While catheter ablation reaches an almost 80% success rate at 12 months for paroxysmal AF patients in many recent trials, regardless of ablation strategy or ablation energy source, the long‐term success rates after ablation for persistent AF do not exceed 50%–55% 6–12 . This may be related to incomplete understanding of the underlying atrial substrate outside the pulmonary veins (PVs).…”
Section: Introductionmentioning
confidence: 99%